Application And Verification Of Halal JAKIM Certificate for Restaurants Apps - Rahmat, Amir Khusaini; Samsudin, Prof Madya Dr Noor Azah (Applied Information Technology And Computer Science, 2022)
The selection of restaurant that satisfies halal status is an important matter for all Muslims. However. However, many restaurants are not responsible for falsifying JAKIM's halal certificate to make a profit without thinking about the details of the halal status of the food served. Apart from that, the dependence on the halal logo issued by JAKIM is very worrying due to the falsifying of JAKIM's halal certificate. Currently, the application for halal certificate and verification of halal status of a food premise can only be performed through the Official Halal Portal of Malaysia Based on the limitation, an Application and Verification of Halal Certificate JAKIM for Restaurant (MyHalal) Apps was developed. With this application, the halal certification can be applied using the smartphone. In addition, food premise halal status can also be accessed on smartphones. Verification of JAKIM's halal status at food premises was obtained by scanning the QR Code. This will facilitate the quick checking process for potential consumers to know the status of the food premises. Next, the app was developed using Android Studio software, the use of a Firebase real -time database, an android smartphone, and the Windows 10 Home operating system. The MyHalal application has been developed successfully and indirectly can be used to provide facilities and information related to halal status for food premises.